Urethral Catheter Biofilms Reveal Plasticity in Bacterial Composition and Metabolism and Withstand Host Immune Defenses in Hypoxic Environment - Yu, Yanbao; Singh, Harinder; Tsitrin, Tamara; Bekele, Shiferaw; Lin, Yi-Han; Sikorski, Patricia; Moncera, Kelvin J.; Torralba, Manolito G.; Morrow, Lisa; Wolcott, Randall; Nelson, Karen E.; Pieper, Rembert (Frontiers in Medicine, 2021)
Biofilms composed of multiple microorganisms colonize the surfaces of indwelling urethral catheters that are used serially by neurogenic bladder patients and cause chronic infections. Well-adapted pathogens in this niche are Escherichia coli, Proteus and Enterococcus spp., species that cycle through adhesion and multi-layered cell growth, trigger host immune responses, are starved off nutrients, and then disperse. Viable microbial foci retained in the urinary tract recolonize catheter surfaces. The molecular adaptations of bacteria in catheter biofilms (CBs) are not well understood, promising new insights into this pathology based on host and microbial meta-omics analyses from clinical specimens. We examined catheters from nine neurogenic bladder patients longitudinally over up to six months. Taxonomic analyses from 16S rRNA gene sequencing and LC-MS/MS-based proteomics revealed that 95% of all catheter and corresponding urinary pellet (UP) samples contained bacteria. CB biomasses were dominated by Enterobacteriaceae spp. and often accompanied by lactic acid and anaerobic bacteria. Systemic antibiotic drug treatments of patients resulted in either transient or lasting microbial community perturbations. Neutrophil effector proteins were abundant not only in UP but also CB samples, indicating their penetration of biofilm surfaces. In the context of one patient who advanced to a kidney infection, Proteus mirabilis proteomic data suggested a combination of factors associated with this disease complication: CB biomasses were high; the bacteria produced urease alkalinizing the pH and triggering urinary salt deposition on luminal catheter surfaces; P. mirabilis utilized energy-producing respiratory systems more than in CBs from other patients. The NADH:quinone oxidoreductase II (Nqr), a Na+ translocating enzyme not operating as a proton pump, and the nitrate reductase A (Nar) equipped the pathogen with electron transport chains promoting growth under hypoxic conditions. Both P. mirabilis and E. coli featured repertoires of transition metal ion (TMI) acquisition systems in response to human host-mediated iron and zinc sequestration. We discovered a new drug target, the Nqr respiratory system, whose deactivation may compromise P. mirabilis growth in a basic pH milieu. Animal models would not allow such molecular-level insights into poly-microbial biofilm metabolism and interactions because the complexity cannot be replicated.